Name-day greeting cards in Łódź worker folklore (A mosaic city: The culture-oriented description, 2023)
The article presents an analysis of name-day greetings card given in the environment of Łódź workers during the interwar period. The author treats greeting cards as a form of environmental folklore, with a specific genre specificity and a clear communication intention, connected with the holistic culture of Łódź workers form the 1920s and 1930s. She also tries to present research material of interest to her in the context of the specific implementation situation, which is the celebration of name-days, referring to the specificity of the celebration of this feast day presented in archival ethnographic materials. The subject of detailed analyses is a collection of name-day cards held at the Bronisława Kopczyńska-Jaworska Ethnographic Archive in Institute of Ethnology and Cultural Anthropology, University of Łódź.